The Use of Phytase Enzyme to Increase Phosphorus Bioavailability of the Diets and Growth Performance of Catfish (Clarias sp) - Mohammad Amin; Dedi Jusadi; Ing Mokoginta (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2011)
ABSTRACT This study was conducted to evaluate the effect of dietary phytase supplementation on phosphorus (P) bioavailability of the diets and growth performance of catfish (Clarias sp) as well as P loading. Four experimental diets were used in this experiment. Diet (A), as a control, was supplemented with inorganic P; diet (B) supplemented with phytase, without inorganic P; diet (C ) supplemented with phytase and citric acid, without inorganic P; and diet (D) without phytase and inorganic P. Phytase was added to the diet at 50 mg/100 g soy bean meal and pollard. Ten fishes with initial body weight of 6.3 ± 0.05 g distributed into an aquarium. Fish fed on the diets for 60 days, there time daily, at satiation. Results indicated that P digestibility increased from 68.55% to 86.1% by the addition of phytase. P digestibility in diet B and C was higher than diet A and D. Daily growth rate of fish from diet B and C were significantly higher than that of diet D, but similar with diet A. Food conversion ratio (FCR) of fish from diet A, B, and C was better than diet D. P concentration in the whole body, bone, and plasma, of fish from diet A,B, and C was higher than diet D, but the Ca and Zn concentration in the whole body, bone, plasma was the same in all treatments. P loading by fish fed diet with phytase ware 58% lower than that of the fish fed control diet. Keyword: Clarias sp, phytase, phosphorus, bioavailability